Sleep Deprivation in Young and Healthy Subjects Is More Sensitively Identified by Higher Frequencies of Electrodermal Activity than by Skin Conductance Level Evaluated in the Time Domain - Posada-Quintero, Hugo F.; Bolkhovsky, Jeffrey B.; Reljin, Natasa; Chon, Ki H. (Frontiers in Physiology, 2017)
We analyzed multiple measures of the autonomic nervous system (ANS) based on electrodermal activity (EDA) and heart rate variability (HRV) for young healthy subjects undergoing 24-hour sleep deprivation. In this study, we have utilized the error awareness test (EAT) every two hours (25 runs total), to evaluate the deterioration of performance. EAT consists of trials where the subject is presented words representing colors. Subjects are instructed to press a button (‘Go’ trials) or withhold the response if the word presented and the color of the word mismatch (‘Stroop No-Go’ trial), or the screen is repeated (‘Repeat No-Go’ trials). We measured subjects’ (N=10) reaction time to the ‘Go’ trials, and accuracy to the ‘Stroop No-Go’ and ‘Repeat No-Go’ trials. Simultaneously, changes in EDA and HRV indices were evaluated. Furthermore, the relationship between reactiveness and vigilance measures and indices of sympathetic control based on HRV were analyzed. We found the performance improved to a stable level from 6 through 16 hours of deprivation, with a subsequently sustained impairment after 18 hours. Indices of higher frequencies of EDA related more to vigilance measures, whereas lower frequencies index (skin conductance leve, SCL) measured the reactiveness of the subject. We conclude that indices of EDA, including those of the higher frequencies, termed TVSymp, EDASymp and NSSCRs, provide information to better understand the effect of sleep deprivation on subjects’ autonomic response and performance.